Click Dehydrogenation of Carbon-Substituted nido-5,6-C2B8H12 Carboranes: A General Route to closo-1,2-C2B8H10 Derivatives - Tok, Oleg L; Bakardjiev, Mario; Štíbr, Bohumil; Hnyk, Drahomír; Holub, Josef; Padělková, Zdenka; Růžička, Aleš (Inorganic chemistry, 2016)
Triethylamine-catalyzed dehydrogenation of carbon-disubstituted dicarbaboranes 5,6-R2-nido-5,6-C2B8H10 [1, where R = H (1a), Me (1b), and Ph (1c)] in refluxing acetonitrile leads to a high-yield (up to 85-95%) formation of a series of dicarbaboranes 1,2-R2-closo-1,2-C2B8H8 (2). The monosubstituted 6-R-nido-5,6-C2B8H11 (3) analogues [where R = Ph (3a), naph (1-naphthyl; 3b), Bu (3c)] afforded 1-R-1,2-closo C2B8H9 (4) isomers [where R = Ph (4a), naph (4b), n-Bu (4c)] as the main products; compounds 4a and 4c were accompanied by 2-R-1,2-C2B8H9 (5) isomers (total yields up to 90%), with the 4/5 molar ratio being strongly dependent on the nature of R (4:1 and 1:1, respectively). All of these cage-closure reactions are supposed to proceed via the stage of the corresponding Et3NH(+) salts of nido anions [5,6-R2-5,6-C2B8H9](-) (1(-)) and [6-R-5,6-C2B8H10](-) (3(-)), which lose H2 and Et3N upon heating (dehydrodeamination). The cage-closure mechanisms leading to closo isomers 2, 4, and 5 have been substantiated by B3LYP/6-31+G* calculations of the reaction profile for a simple 1a(-) → 2a + H(-) conversion. All of the compounds isolated have been characterized by multinuclear ((11)B, (1)H, and (13)C) NMR spectroscopy, mass spectrometry, and elemental analyses, and the structure of 1-Ph-closo-1,2-C2B8H9 (4a) was established by an X-ray diffraction study.